Prevalence and Clinical Characteristics of Hereditary Colorectal Cancer in Brunei Darussalam: A Retrospective Study - Awang Josli, Muhammad Hazman; Ghani, Hazim; Ya Chee, Lim; Chong, Vui Heng; Kiong Lu, Shir; King Ong, Sok; Abdul Rahman, Hanif; Idris, Fazean (Asian Pacific Journal of Cancer Care, 2024)
Introduction: Hereditary colorectal cancer (CRC) is associated with early disease onset and an increased risk of developing other malignancies. This study aimed to estimate the prevalence of hereditary CRC over a six-year period and report the sociodemographic and clinical profiles of affected patients in Brunei Darussalam. Methods: This retrospective review of data from 146 patients diagnosed with CRC between January 2017 and December 2022 was conducted at The Brunei Cancer Centre. Suspected or confirmed hereditary CRC cases were identified from the 146 cases based on microsatellite instability (MSI) assay testing, immunohistochemistry (IHC) four-panel staining for mismatch repair (MMR) genes MLH1, MSH2, MSH6, and PMS2, and BRAFV600E test results. Results: Among the 146 CRC patients, 41.7% (n=61) underwent MSI testing. Of these, 7.5% (n=11) showed high microsatellite instability (MSI-H), with two cases associated with Lynch syndrome. Among the 11 patients with suspected or confirmed hereditary colorectal cancer, the majority presented with abdominal pain prior to diagnosis (81.8%; n=9). Stage 2 cancer was the most common stage at diagnosis (36.4%; n=4), followed by moderately differentiated tumors (72.7%; n=8). The most frequent tumor location was the cecum (36.4%; n=4). All patients underwent surgery as first-line management, and over half (54.5%; n=6) received chemotherapy. Conclusion: This study found that 7.5% of CRC cases seen at a tertiary cancer center over a six-year period were suspected or confirmed to be hereditary. The lack of widespread genetic testing in local settings suggests that the actual prevalence of hereditary CRC in Brunei Darussalam might be higher. Further research into genetic testing and early screening strategies for hereditary CRC is needed.